HALAL TOURISM DEVELOPMENT STRATEGY IN DKI JAKARTA POST THE END OF PANDEMIC COVID 19 - Sutarman, Asep (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2024)
The purpose of this study is to identify a strategy for developing halal tourism, especially in the DKI Jakarta area, taking into account several factors, including local wisdom, communication patterns, tourist satisfaction and interest in visiting. This research data was obtained by distributing questionnaires to local and foreign tourists who visited halal tourism in DKI Jakarta (Taman Impian Jaya Ancol, TMII, Kota Tua and Thamrin City) after the Covid 19 pandemic. The sampling technique used was purposive and convenience sampling. (Collection of information from members of the population who agree and are willing to provide information). The data apply SEM-PLS to analyze the proposed relationship model. The results of this study are communication patterns, local wisdom and tourist satisfaction affect the interest of tourists to visit halal tourism in DKI Jakarta. Communication patterns and local wisdom have a significant positive effect on tourist satisfaction on halal tourism in DKI Jakarta. Likewise, local wisdom has a positive impact on communication patterns. Tourist satisfaction can be a good mediating variable for local wisdom and communication patterns in influencing tourist interest in visiting. Keywords: communication patterns, local wisdom, tourist satisfaction, interest in visiting